Comprehensive training in robotic surgery. Issue 1 (January 2019) - Brook, Nicholas R.; Dell'Oglio, Paolo; Barod, Ravi; Collins, Justin; Mottrie, Alexandre
Abstract : Purpose of review: Robotic training in urology can be poorly structured, lack a basic skills foundation, and may not include teaching in important nontechnical human factor skills vital to the safe delivery of robotic care. Assessment of acquired skills is not routine. There is a need for structured and standardized curricular to deliver validated training and final assessment. The present reviews the current literature on training methods for robotic surgery, and examines the evidence for their effect on performance, where available. Recent findings: There is good evidence for the beneficial effect of dry lab simulators on robotic skills acquisition, but less for cadaveric and animal models. Two urological authorities have developed comprehensive curricula for robotic training that take a novice robotic surgeon through the full stages of robotic skills acquisition. These are in the early stages of development and validation but have stimulated the development of curricula in other specialties. Summary: The future landscape for robotic urology training is likely to include structured, mandated, and centralized training, possibly administered by urological organizations. There will be roles for telementoring, advanced education for robotic trainers, and regular revalidation of expert robotic surgeons.